2019
DOI: 10.1371/journal.pone.0215428
|View full text |Cite
|
Sign up to set email alerts
|

Usability of rectal swabs for microbiome sampling in a cohort study of hematological and oncological patients

Abstract: Objectives Large-scale clinical studies investigating associations between intestinal microbiota signatures and human diseases usually rely on stool samples. However, the timing of repeated stool sample collection cannot be predefined in longitudinal settings. Rectal swabs, being straightforward to obtain, have the potential to overcome this drawback. Therefore, we assessed the usability of rectal swabs for microbiome sampling in a cohort of hematological and oncological patients. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
4
30
1
2
Order By: Relevance
“…It is also possible that the storage of the samples directly after collection (freezing at −20 • C) before transport in a cold box and then freezing at -80°C was not optimal for preservation of DNA, but this was the same for all samples collected at the race. Although rectal swabs have been shown to give reliable results in studies of the intestinal microbiota in humans [29], direct comparison of the results from our study with those of other studies may be difficult due to the major influence of extraction method on composition and diversity [30,31].…”
Section: Discussionmentioning
confidence: 74%
“…It is also possible that the storage of the samples directly after collection (freezing at −20 • C) before transport in a cold box and then freezing at -80°C was not optimal for preservation of DNA, but this was the same for all samples collected at the race. Although rectal swabs have been shown to give reliable results in studies of the intestinal microbiota in humans [29], direct comparison of the results from our study with those of other studies may be difficult due to the major influence of extraction method on composition and diversity [30,31].…”
Section: Discussionmentioning
confidence: 74%
“…However, the opposite is the case with animals, as most fecal samples are obtained from the environment. For animals, rectal swabbing is typically difficult and involves a great deal of planning and expertise [ 53 ]. A good technique for sample collection is that which reduces DNA lyses or alteration for molecular studies, as many studies have shown how important it is for sample collection and storage, library preparation, and DNA extraction using a standardized procedure [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, we were limited by the original SPREAD population, in which few subjects 463 received only a single antimicrobial during the course of the study; this makes it difficult to say 464 whether the temporal variability we observed was widespread in the cohort, although the fact that 465 there were frequently high pathobiont levels observed in the larger metagenomics dataset we used 466 to test our multiple linear regression suggests that this may be the case. Third, in this study we 467 worked with rectal swabs, which are similar but not identical to fecal samples and may be 468 susceptible to cross-contamination from urinary pathogens or skin flora, particularly in incontinent 469 advanced dementia patients [152][153][154][155]. Fourth, metagenomic assembly has limitations.…”
Section: Prediction Of Arg Density From Species Abundances 317mentioning
confidence: 99%